Molecular confirmation of Dicrocoelium dendriticum in the Himalayan ranges of Pakistan. (April 2021) - Khan, Muhammad Asim; Afshan, Kiran; Nazar, Muddassar; Firasat, Sabika; Chaudhry, Umer; Sargison, Neil D.
Abstract: Lancet liver flukes of the genus Dicrocoelium (Trematoda: Digenea) are recognised parasites of domestic and wild herbivores. The aim of the present study was to confirm the species identity of Dicrocoeliid flukes collected from the Chitral valley in the Himalayan ranges of Pakistan. The morphology of 48 flukes belonging to eight host populations was examined; but overlapping traits prevented accurate species designation. Phylogenetic comparison of published D. dendriticum ribosomal cistron DNA, and cytochrome oxidase-1 (COX-1) mitochondrial DNA sequences with those from D. chinensis was performed to assess within and between species variation and re-affirm the use of species-specific single nucleotide polymorphism markers. PCR and sequencing of 34 corresponding fragments of ribosomal DNA and 14 corresponding fragments of mitochondrial DNA from the Chitral valley flukes, revealed 10 and 4 unique haplotypes, respectively. These confirmed for the first time the molecular species identity of Pakistani lancet liver flukes as D. dendriticum . This work provides a preliminary illustration of a phylogenetic approach that could be developed to study the ecology, biological diversity, and epidemiology of Dicrocoeliid lancet flukes when they are identified in new settings. Highlights: First molecular confirmation of Dicrocoelium dendriticum in Himalayan Pakistan. Use of ribosomal and mitochondrial DNA phylogenetic markers. Demonstration of the complementary value of morphological and molecular speciation methods for Dicrocoeliid flukes.